족보의 계보를 통해 본 친족 결집의 이상과 현실 — 합천이씨 족보를 중심으로 — - 한상우 (사림, 2018)
Hapcheon Lee clan, a typical elite family in local society, compiled about 60 kinds of genealogies after the 17th century. Prior studies regarded compiling genealogies as core evidence of regimentation and organization of patrilineal kin. That is because, they comprehended genealogies and its’ contents from ideological point of view such as Neo-Confucianism and patriarchism. However, in the case of Hapcheon Lee, genealogies were not a result of regimentation, but the product of dispute between clan members. In this study, I analyze the prefaces, introductory notes and pedigrees on about 20 kinds of their genealogies. The Hapcheon Lee was divided into several lineages. Two powerful lineages in the clan heated argument on their “place of origin (本貫)” after the 18th century. This dispute was a competition for leadership in compiling for next genealogy. One lineage members did not record the other lineage members on their own genealogies, so the other lineage members compiled their own without discussion. That was the reason why the clan had such a many kinds of genealogy. The dispute brought intervention of the Ministry of Rites, but the disunion among clan members was maintained until the early 20th century. Even in a same lineage, the compilers from powerful families were reluctant to include middle class or lowborn members. It means that studies on genealogies and kinship need to be conducted with not only rhetoric, but also with composition and contents. Even though all genealogies mentioned harmony of kin members on the preface, it is hard to find which all kin members including non-elite members were recorded equivalently on the text. The compilers of genealogies dreamed the regimentation of clan, but this ideal was not easy to be realized on the genealogies in Joseon society which maintained the social hierarchy system till the end.
Keywords: 족보; 친족집단; 호적; 동성촌락; 가문; genealogy; kinship; household register; same family-name village; lineage